Interfacial characteristics and strengthening mechanisms of novel copper-interlayered Ti-6Al-4V wire-reinforced aluminum matrix composites - Zixuan Dou; Lisheng Zhong; Chao Deng; Congcong Ren; Kaiyuan Hu; Kai Wang (Journal of Materials Research and Technology)
The 5xxx series aluminum alloys are widely used in industry due to their excellent weldability and corrosion resistance. However, their relatively low tensile strength (240–400 MPa), compared to 2xxx (410–510 MPa) and 7xxx series alloys (570–690 MPa), restricts their application in high-stress environments. To address the mechanical property limitations of 5052 aluminum alloy, a novel strategy combining copper electroplating, gradient thermal processing, and hot-dip metal mold casting was developed to fabricate copper-interlayered Ti-6Al-4V wire-reinforced aluminum matrix composites (Cu-TC4/AMC). Quantitative analysis shows that Cu-TC4/AMC treated at 860 °C for 45 min exhibits a 91.9 % and 22.6 % increase in strength compared to the aluminum matrix and conventional composites, respectively. The copper buffer layer significantly alters interfacial evolution by suppressing Al-Ti interdiffusion through a kinetic barrier effect and redistributing stress due to its ductility. The multiscale interfacial design, achieved through controlled electrodeposition and non-isothermal sintering, addresses the longstanding trade-off between reinforcement efficiency and interfacial embrittlement in titanium-aluminum systems. These findings are supported by X-ray diffraction and EBSD analysis. This work demonstrates an innovative strategy for balancing strength and ductility in aluminum matrix composites, offering new insights into interfacial design for high-performance structural materials.